A Semiotic Analysis on Inaco Product Packaging - Frina Diniarta Nur; Rini Adriati; Ivan Ferdinand (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
This study aims to identify semiotic signs present on the packaging of Nata de Coco. Utilizing a qualitative approach, the research draws upon Saussure's signifier and signified theory as outlined by Chandler (2022). Through analysis, ten semiotic signs were identified on the packaging, including the overall design, company logo, Wonderful Indonesia logo, Superbrands logo, Top Brand logo, Halal MUI logo, Mr. Mutu logo, International Food Safe symbol, International Resin Identification (7 other) Code symbol, and Do Not Litter icon. These findings shed light on the symbolic elements utilized in packaging design and their significance in communicating messages to consumers.